2014
DOI: 10.1007/s12630-014-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium following transcatheter aortic valve implantation: a historical cohort study

Abstract: Patients undergoing TA-TAVI had a markedly increased incidence of postoperative delirium compared with patients undergoing TF-TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
(32 reference statements)
5
30
1
Order By: Relevance
“…The incidence of delirium after TAVI in our study (28.1%) is comparable to the incidence reported by previous studies examining delirium after TAVI (12–53%)14 15 or cardiac surgery (26–66%) 24–27. The observed incidence of delirium in our study may have been influenced by several factors: (a) transfer of the patient (from intensive care unit to cardiac care unit), (b) general anaesthesia, (c) strict patient follow-up by the geriatric consultation team and (d) preventive guidelines.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The incidence of delirium after TAVI in our study (28.1%) is comparable to the incidence reported by previous studies examining delirium after TAVI (12–53%)14 15 or cardiac surgery (26–66%) 24–27. The observed incidence of delirium in our study may have been influenced by several factors: (a) transfer of the patient (from intensive care unit to cardiac care unit), (b) general anaesthesia, (c) strict patient follow-up by the geriatric consultation team and (d) preventive guidelines.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the access site may have influenced the incidence of delirium, as previous investigators showed difference in incidence of delirium related to the access site of the TAVI procedure (transfemoral vs transapical) 14. Moreover, the preventive use of haloperidol in 5/89 patients may have influenced the incidence of delirium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And although the list of possible risk factors for PD after SAVR remains long, the variables identified in this study such as age, a history of coronary artery disease, a need for an intra-aortic balloon pump preoperatively, and greater PRBC transfusions have all previously been cited as candidate risk factors for PD with on-pump surgery. 3,6,8,10,19 And although there are only a few studies available describing PD after TAVR, the data available thus far are consistent with those from this investigation suggesting that PD is an equally prevalent complication for TAVR, particularly when performed using alternative access techniques, 20,21 It is possible that despite the fact that TAVR may be a less-invasive procedure than SAVR, given the high-risk patient population for whom TAVR is currently restricted to as a procedural option, the incidence of PD following TAVR will remain high. The results from propensity-matched patients within this study suggest that a typical patient undergoing TAVR, with numerous comorbidities, would likely have an even higher likelihood of PD if offered an SAVR approach.…”
Section: Discussionsupporting
confidence: 85%